Social Media and Political Propaganda: A double-edged Sword for Democratic Consolidation in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
Social media serves as a powerful tool for politicians to engage with voters and drive the conversation in their favor. Still, the authenticity and accuracy of online information can be questionable as there are currently no mechanisms in place to regulate or sanction the spread of false or misleading information on social media, making it even more challenging to combat the proliferation of political propaganda. Also, the prevalent availability and lack of mechanisms to checkmate it allows individuals and political actors to spread misleading information which causes a significant problem. Therefore, the trust of this paper was to examine the role of social media platforms specifically Facebook and Twitter, as well as the gaps and challenges in identifying the dissemination and amplification of political propaganda in Nigeria. The study utilized qualitative research and was analyzed descriptively. The study revealed that Social media promotes political propaganda and manipulates the perception of the electorate which changes the outcome of elections.  Ultimately, the paper argues that a comprehensive approach is needed to regulate the spread of political propaganda on social media platforms in Nigeria, which include; the creation of digital literacy programs that focuses on media literacy and online etiquette, deeper cooperation between the Nigerian government and social media platforms to curb the spread of political propaganda, the establishment of legal frameworks to punish offenders, mitigating political propaganda are some of the recommendations highlighted in this study.